2014
DOI: 10.1111/jnc.12637
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol as a causative factor in Alzheimer's disease: a debatable hypothesis

Abstract: High serum/plasma cholesterol levels have been suggested as a risk factor for Alzheimer's disease (AD). Some reports, mostly retrospective epidemiological studies, have observed a decreased prevalence of AD in patients taking the cholesterol lowering drugs, statins. The strongest evidence causally linking cholesterol to AD is provided by experimental studies showing that adding/reducing cholesterol alters amyloid precursor protein (APP) and amyloid beta-protein (Ab) levels. However, there are problems with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(151 citation statements)
references
References 166 publications
(294 reference statements)
2
147
1
1
Order By: Relevance
“…Yet, the Km is significantly more favorable for the reaction in bicelles, which contains CHAPSO, a cholesterol mimic. Cholesterol is a modulator of both membranes (51,52) and C100 catalysis (53)(54)(55)(56)(57). Indeed, relevant regions of C100 are partitioned well inside the lipid bilayer and specifically bind cholesterol (53).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the Km is significantly more favorable for the reaction in bicelles, which contains CHAPSO, a cholesterol mimic. Cholesterol is a modulator of both membranes (51,52) and C100 catalysis (53)(54)(55)(56)(57). Indeed, relevant regions of C100 are partitioned well inside the lipid bilayer and specifically bind cholesterol (53).…”
Section: Discussionmentioning
confidence: 99%
“…3) [61,62]. APP and the secretases are integral membrane proteins, and numerous studies have demonstrated a role of cholesterol in the proteolytic processing of APP and the generation of Aβ [63,64,65,66]. However, the exact molecular mechanisms and the relevance of cholesterol in AD pathogenesis is still under debate [63,64,65,66].…”
Section: S1p - a Potential Mediator In The Pathogenesis Of Alzheimer'mentioning
confidence: 99%
“…APP and the secretases are integral membrane proteins, and numerous studies have demonstrated a role of cholesterol in the proteolytic processing of APP and the generation of Aβ [63,64,65,66]. However, the exact molecular mechanisms and the relevance of cholesterol in AD pathogenesis is still under debate [63,64,65,66]. The role of lipid homeostasis in the brain, particularly that of membrane lipids, in AD pathogenesis has been recognized and considered in multitudinous studies [67,68].…”
Section: S1p - a Potential Mediator In The Pathogenesis Of Alzheimer'mentioning
confidence: 99%
“…This increase in plasma cholesterol level in HFD-induced amnesia corroborated with other study results that elevated serum cholesterol level could be an important risk factor for AD. [4][5][6] Atorvastatin and simvastatin in 5 mg/kg b.w. dose significantly decreased the plasma cholesterol level whereas piracetam did not show any significant change in plasma cholesterol level.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] It appears that cholesterol turnover plays an important role in the deposition and clearance of amyloid peptide in brain. [3][4][5][6] Oxygen free radicals produced within the neurons National Journal of Physiology, Pharmacy and Pharmacology 1294 2017 | Vol 7 | Issue 12 can cause tissue damage and are also implicated in aging and neurodegenerative process. [7,8] The most widely used treatments for AD at present are the reversible acetylcholinesterase inhibitors, which aim at prolonging cognitive functions through decreased degradation of acetylcholine at synaptic cleft.…”
Section: Introductionmentioning
confidence: 99%